Evaluation of 86 Patients Whom Death While Being Followed up with Pre-Diagnosis of Covid-19 - Büşra Çalışır; Nilay Çöplü; Çetin Kılınç; Melike Yaşar Duman; Sedat Gülten; Abdullah İbrahim Çalışır; Ahmet Özden (Medical Laboratory Technology Journal, 2021)
The Coronavirus-19 pandemic continues at full speed, and the number of patients who die from Covıd-19 is increasing. It was aimed to evaluate the demographic information and laboratory findings of 86 patients who died while being followed up in our hospital with a pre-diagnosis of Covıd-19. Identifying these characteristics of deceased patients will be essential to guide clinicians in identifying critically ill patients. Data on demographic information, comorbidities, time from hospitalization to death, molecular test results, thorax CT findings, biochemical findings, culture, antibiotic susceptibility, and the given treatments of the cases were collected from the electronic system Kastamonu Training and Research Hospital. While the RT-PCR test of 21 of the cases was positive, in 9 of the cases, control PCR tests were negative after a while. The CT results of 18 of the 21 initially RT-PCR positive cases were compatible with Covid-19, and the CT result of 3 could not be reached. When the blood test results of the cases were examined, neutrophil increase, white blood cell increase, lymphocyte reduction, and inflammatory markers increase were determined. A total of 43 bacterial growths were found in 21 cases. It has been observed that deaths in patients who were followed up with the pre-diagnosis of Covıd-19 generally occur in older people, males, and those with underlying diseases. It was thought that the cause of death could be underlying diseases, pathologies caused by inflammation, and secondary bacterial infections in addition to viral infection. Clinicians should be more careful about elderly patients, patients with secondary bacterial infections, or patients with neutrophilia, lymphopenia.